Incentive-compatible voting rules with positively correlated beliefs - Arunava Sen; Mohit Bhargava; Dipjyoti Majumdar (Theoretical Economics, 2015)
We study the consequences of positive correlation of beliefs in the design of voting rules in a model with an arbitrary number of voters. We propose a notion of positive correlation, based on the likelihood of agreement of the k best alternatives (for any k) of two orders called TS correlation. We characterize the set of Ordinally Bayesian Incentive-Compatible (OBIC) (d'Aspremont and Peleg (1988)) voting rules with TS-correlated beliefs and additionally satisfying robustness with respect to local perturbations. We provide an example of a voting rule that satisfies OBIC with respect to all TS-correlated beliefs. The generally positive results contrast sharply with the negative results obtained for the independent case by Majumdar and Sen (2004) and parallel similar results in the auction design model (Cremer anf McLean (1988)).
Keywords: C70; C72; 330; Voting rules; ordinal Bayesian incentive compatibility; positive correlation; robustness with respect to beliefs